Aesthetic Criteria: Gombrich and the Philosophies of Science of Popper and Polanyi - Richmond, Sheldon (Amsterdam Rodopi, 1994)
Dr. Richmond's book examines deftly the aesthetic theory of leading art historian and critic, Sir Ernst Gombrich. Though in the psychology of art and in related matters Gombrich is an avowed follower the rationalist philosophy of science of Sir Karl Popper, in aesthetics proper he follows ideas first propounded in the irrationalist philosophy of science of Michael Polanyi. Dr. Richmond presents succinctly the ideas of these three great thinkers and finds here an unexpected irrationalist streak in the rationalistic works of Gombrich. (Joseph Agassi)
Keywords: Gombrich, Ernst -- 1909-2001; Popper, Karl -- 1902-1994; Polanyi, Michael -- 1891-1976; 20th Century (1901-2000); Esthetics; Philosophy; Natural science